2007
DOI: 10.3171/foc-07/11/e10
|View full text |Cite
|
Sign up to set email alerts
|

Combined transconjunctival–eyebrow approach providing minimally invasive access to all orbital quadrants

Abstract: ✓Surgical approaches to treat orbital disease should provide a good exposure of intraorbital anatomical structures, allow their functional preservation, and provide good cosmetic results. The authors describe a minimally invasive, combined transconjunctival–eyebrow approach to all orbital quadrants in a step-wise manner. The indications, advantages, and limitations of the technique are highlighted. A transconjunctival approach via the postseptal area is described. It allows exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…(D) 3D picture of the area described in (C). transantral, and transnasal transethmoidal approaches (Chang et al, 2003;Delfini et al, 1992;Goldberg et al, 2007;Graham et al, 2002;Karaki et al, 2006;Kingdom and Delgaudio, 2003;Kiratli et al, 2005;Koerbel et al, 2007;Metson and Pletcher, 2006;Monin et al, 2005;Numa and Kawamoto, 2007;Perry, 2006;Schick et al, 2003;Hassler, 2004, 2005;Tsirbas et al, 2005). Karaki et al (2006) presented the advantages and disadvantages of various approaches, and underlined the importance of the endoscopic endonasal approaches to lesions situated in the inferomedial aspect of the orbital apex.…”
Section: Discussionmentioning
confidence: 97%
“…(D) 3D picture of the area described in (C). transantral, and transnasal transethmoidal approaches (Chang et al, 2003;Delfini et al, 1992;Goldberg et al, 2007;Graham et al, 2002;Karaki et al, 2006;Kingdom and Delgaudio, 2003;Kiratli et al, 2005;Koerbel et al, 2007;Metson and Pletcher, 2006;Monin et al, 2005;Numa and Kawamoto, 2007;Perry, 2006;Schick et al, 2003;Hassler, 2004, 2005;Tsirbas et al, 2005). Karaki et al (2006) presented the advantages and disadvantages of various approaches, and underlined the importance of the endoscopic endonasal approaches to lesions situated in the inferomedial aspect of the orbital apex.…”
Section: Discussionmentioning
confidence: 97%
“…Transconjunctival approach combined with eyebrow incision can provide less invasive access to all orbital quadrants except for lesions with intracranial or intrafacial tumor extension and pathological entities located purely in the orbital apex. 1,5) In the present case, preoperative neuroimaging revealed that the lesion involved all orbital quadrants, although mainly the medial compartment, and extended to the orbital apex. In addition, the tumor was irregularly shaped O. Akiyama et al…”
Section: Discussionmentioning
confidence: 96%
“…1,3,5,10) In contrast, conservatively managed patients remained stable during a followup period of 3-10 years. 7) Present case showed progressive ocular symptoms caused by the orbital lesion and underwent a surgical exploration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The central approach has two variants and may be selected for biopsy or removal of lesions located in the intraorbital segment of the optic nerve or located in the midportion of the orbit. Modern neurosurgery targets the best possible minimal invasive surgical outcome with minimal tissue damage and maximal patients' cosmetic satisfaction, pain, and functional outcomes (Koerbel et al, ; Abdel Aziz et al, ; Reisch et al, ; Tatarli et al, ; Ulutas et al, ). The recently introduced endoscopic approaches to the orbit apex offers significant advantages and better surgical outcomes over external approaches, and was suggested to be the preferred approach for all medial and inferior lesions (Stokken et al, ).…”
Section: Discussionmentioning
confidence: 99%